HUBUNGAN KONDISI EKONOMI ORANG TUA DENGAN HASIL BELAJAR EKONOMI PESERTA DIDIK KELAS X SMAN 10 BANDAR LAMPUNG - Sahara, Kiki Syarah; RB, Muhammad; Meladi, Meladi (LPPM STKIP PGRI Bandar Lampung, 2019)
The problem in this study is the low student learning outcomes, the low interest of students in learning and the economics of parents that influence student learning outcomes. The purpose of this study was to determine the relationship of economic conditions of parents with the economic learning outcomes of students of Social Sciences class X even semester SMA 10 Bandar Lampung 2018/2019 academic year. In this study, the author uses a quantitative descriptive method because the score of the variable is in the form of numbers which will then be processed using a statistical formula to produce a value. The population in this study were students of class X. IPS which amounted to 88 students and the samples tested in this study also amounted to 22 students. Data analysis technique to test the hypothesis that the author uses is product moment correlation. Based on the results of hypothesis testing showing thit> ttab or 15.32> 1.72, Ho is rejected, meaning that there is a significant relationship between the economic condition of parents and the economic learning outcomes of IPS X class students in the even semester of SMA Bandar Lampung 2018 / 2019. There is a fairly high correlation between the economic conditions of parents and the economic learning outcomes of IPS X-class students in the even semester of SMA Bandar Lampung 10 in the academic year 2018/2019. This is based on the results of hypothesis testing showing rxy = 0.96.